Educational robotics with tangible programming: A digital circuit for blocks communication with code and visual feedback transfer capabilities - Salles, Jessica Toledo [UNESP]; Cabral, Cristiane Pelisolli; Aragon, Rosane; Da Silva Simoes, Alexandre [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
A large number of robotic kits is commercially available for children education nowadays. Regarding the programming possibilities of these kits, they are usually divided into three categories: i) textual languages based kits, ii) digital blocks based kits and iii) tangible blocks based kits. In tangible blocks kits, the programming instructions are represented by physical-touchable-elements like blocks, cards or buttons. Since these are concrete objects, they are usually more playful and accessible for young children mainly in the concrete operational stage. Another relevant aspect in robotic kits is the possibility for children to follow the code execution at runtime. This process may be crucial for comprehending the programming process and for developing debugging abilities. In tangible programming based kits, this visual tracking is far more complex than in textual or digital blocks based kits since it typically requires the transmission of information between a lot of distinct physical pieces. The present work proposes and discusses the implementation of a digital electronic circuit with bluetooth communication designed for educational robotics kit and capable to provide a visual feedback. Results demonstrate that the proposed circuit is functional and feasible for embedding in robotic kits at a low cost.
Keywords: digital circuits; educational robotics; programming; tangible blocks; visual feedback